FAKTOR YANG MEMPENGARUHI CAPITAL STRUCTURE DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Tanzil, Kezia Agustilia; Viriany, Viriany (Jurnal Paradigma Akuntansi, 2025)
This research is aims to empirically examine the effect of asset structure, liquidity, and company size on capital structure with profitability as a moderating variable for food and beverage companies listed on the IDX for the 2019-2021 period. In this study, data were used from 20 food and beverage companies listed on the IDX that had been selected using a purposive sampling method for a period of 3 years. In this research, Microsoft Excel and Eviews Student ver 12 software is used to processed the data. Conclusions of this research are asset structure had a positive and significant effect on capital structure, liquidity and firm size had a negative and insignificant effect on capital structure, profitability could moderate the effect between asset structure and company size on capital structure, and profitability cannot moderate the effect of liquidity on capital structure.